1986
DOI: 10.1128/jb.166.3.1128-1130.1986
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular organization of F1-ATPase isolated from Clostridium thermoaceticum as revealed by electron microscopy

Abstract: Membrane vesicles and the Fl-ATPase from Clostridium thermoaceticum were examined by electron microscopy. Fl-ATPase particles projecting from the vesicles have a diameter of 10 to 12 nm. The Fl-ATPase has an 3,3Y8b structure. The a and , subunits are most likely arranged in an alternating sequence around a central protein mass consisting of the -y and 8 subunits.Clostridium thermoaceticum is an obligate anaerobic thermophile that carries out homoacetogenic fermentation of sugars (10). It also grows autotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 16 publications
3
46
0
Order By: Relevance
“…With cellulolytic organisms such as Tichoderma reesei, Neocallismastix frontalis, Pseudomonas fluorescens, Cellulomonas fimi, Fibrobacter succinogenes, and Ruminococcus flavefaciens, it is not certain whether the enzymes essential for the degradation of crystalline cellulose function individually or whether they are present on the cell or substrate surface as a complex (1,15,20). There is evidence that in Clostridium thernocellum as well as in Clostridium strain C7, the enzymes are present in a complex, termed the "cellulosome" (3, 18,19,22,23). There is evidence that the enzymes present in Clostndium cellulovorans are also present in a complex.…”
mentioning
confidence: 99%
“…With cellulolytic organisms such as Tichoderma reesei, Neocallismastix frontalis, Pseudomonas fluorescens, Cellulomonas fimi, Fibrobacter succinogenes, and Ruminococcus flavefaciens, it is not certain whether the enzymes essential for the degradation of crystalline cellulose function individually or whether they are present on the cell or substrate surface as a complex (1,15,20). There is evidence that in Clostridium thernocellum as well as in Clostridium strain C7, the enzymes are present in a complex, termed the "cellulosome" (3, 18,19,22,23). There is evidence that the enzymes present in Clostndium cellulovorans are also present in a complex.…”
mentioning
confidence: 99%
“…The strain C7 cylindrical particles seem to be composed of two rings of subunits with a cleft or groove visible at the juncture of the two rings. Similar flattened cellulosomes, consisting of subunits arranged so that they formed two halves of the cellulosome separated by a groove, were observed by Mayer and co-workers (18) in cultures of C. thermocellum JW20. The existence of similar ultrastructural features in multiprotein complexes from different cellulolytic bacteria suggests that a particular arrangement of the proteins within the complexes is required for crystalline cellulose hydrolysis.…”
Section: Discussionmentioning
confidence: 60%
“…The particles observed by electron microscopy in negatively stained preparations of the 700,000-Mr enzyme complex of strain C7 are similar in ultrastructure to cellulosomes of C. thermocellum (6,13,18). Both the strain C7 particles and the cellulosomes are composed of subunits.…”
Section: Discussionmentioning
confidence: 67%
“…The observation of cell surfaces at the late exponential growth phase by scanning electron microscopy (SEM) revealed that the cells adhered to xylan (Fig. 5A), similar to the cells of the cellulosome producing anaerobic bacterium, C. thermocellum, which is a cell associated entity that mediates the adhesion of the bacterium to cellulose (Lamed et al, 1987;Mayer et al, 1987), whereas the surface of the cells of strain B-6 at the late stationary growth phase lacked such structures because the multienzyme complex was released into the medium from the cell surfaces (Fig. 5B).…”
Section: Characteristics Of P Curdlanolyticus B-6 Multienzyme Complexmentioning
confidence: 99%